METODE PROYEK TERHADAP PERILAKU KERJASAMA ANAK AUTIS - Putri Fatmawati, Dwi (Jurnal Pendidikan Khusus, 2016)
ABSTRACT This research was formed background the importance of social behavior to be developed to autism children since early age. One of the social behavior aspects which needed to be developed was cooperation behavior. It seemed to the autism children’s behavior which was very individualist and closed in finishing everything. Through project method autism children were directed to finish the class picket duty with cooperating together with classmates. This research had purpose to prove the influence of project method toward cooperation behavior to autism children of group B in TK Insani Mandiri Sidoarjo. This research used quantitative approach with experiment kind with single subject research and the research arrangement was A-B-A. The subject was all autism children of group B in Insani Mandiri Sidoarjo numbering 1 child whose social behavior of cooperation aspect needed to be developed. The data collection technique used observation. The data analysis technique used descriptive statistic with visual analysis in condition and visual analysis among condition. The research result indicated that project method could decrease cooperation refusal behavior to autism children of group B in TK Insani Mandiri with the average frequency to baseline phase (A1) 3,5, intervention phase (B) 0 and repeating baseline observation phase (A2) 2,5. From the overlap data it indicated that the small percentage value was 20% which meant project method influenced toward cooperation refusal behavior to autism children of group B in TK Insani Mandiri Sidoarjo.   Keywords : Project method, cooperation behavior